2021
DOI: 10.1093/ije/dyab170
|View full text |Cite
|
Sign up to set email alerts
|

Maternal education and cognitive development in 15 European very-preterm birth cohorts from the RECAP Preterm platform

Abstract: Background Studies are sparse and inconclusive about the association between maternal education and cognitive development among children born very preterm (VPT). Although this association is well established in the general population, questions remain about its magnitude among children born VPT whose risks of medical and developmental complications are high. We investigated the association of maternal education with cognitive outcomes in European VPT birth cohorts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 65 publications
2
25
0
1
Order By: Relevance
“… 3 For example, a recent meta-analysis of European preterm cohorts showed that, compared with families where mothers had a bachelors or higher degree, standardised mean differences of cognitive scores for children born extremely preterm were 0.24 (95% CI 0.02 to 0.46) lower in families where mothers had an upper secondary or short tertiary level of education, and 0.57 (95% CI 0.34 to 0.76) lower when mothers had only primary or lower secondary education. 20 …”
Section: Rates Of Extreme Preterm Births Survival and Associated Morb...mentioning
confidence: 99%
“… 3 For example, a recent meta-analysis of European preterm cohorts showed that, compared with families where mothers had a bachelors or higher degree, standardised mean differences of cognitive scores for children born extremely preterm were 0.24 (95% CI 0.02 to 0.46) lower in families where mothers had an upper secondary or short tertiary level of education, and 0.57 (95% CI 0.34 to 0.76) lower when mothers had only primary or lower secondary education. 20 …”
Section: Rates Of Extreme Preterm Births Survival and Associated Morb...mentioning
confidence: 99%
“…The GA/BW inclusion criteria in these studies were highly varied as shown in Table 2 with 27 different combinations. The most common were BW <1500 g (24 cohorts), GA <32 weeks (12), GA <33 weeks (12) and BW<1000 grams (12). Few cohorts (2) had GA <28 weeks as an inclusion criterion.…”
Section: Resultsmentioning
confidence: 99%
“…11 This is of concern because disadvantaged families face higher risks of VPT birth 11 and social disadvantage is associated with worse long-term cognitive outcomes. 12 Systematic reviews have adopted different approaches, with some including all studies based on GA and/or BW, while others have aimed to reduce heterogeneity by selecting only studies that used GA inclusion criteria. In a review of five systematic reviews with metaanalyses on the topic of VPT birth and cognition, we previously showed that investigators' methodological choices with regard to inclusion and exclusion criteria for primary studies resulted in minimal overlap in the included studies across systematic reviews.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, markers of neonatal morbidity such as supplemental oxygen use at 28 days/36 weeks postmenstrual age and the ultrasound identification of preterm brain injury were also associated with a 2-3 point decrement in IQ. In a separate meta-analysis, the effect of maternal education produced a consistent effect at different ages and in different gestational groups [2]. Reflecting the birth years of the cohorts (1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986)(1987)(1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995), the mean age at assessment ranged from 19 to 30 years.…”
Section: Cognitionmentioning
confidence: 89%